ANTHROPOMETRY AND PREVALENCE OF OBESITY AMONG KOM TRIBAL FEMALE OF REPRODUCTIVE AGE GROUP (International Journal of Food and Nutritional Sciences, 2025)
Background: Obesity among tribal women is a growing health concern influenced by lifestyle, limited healthcare access, and nutritional transition leading to higher calorie intake and lower physical activity. Obesity increases the risk of non-communicable diseases like Diabetes, Hypertension, Cardiovascular disease and certain type of Cancers Objective: The study attempt to assess anthropometry and prevalence of obesity among kom tribal female of reproductive age group. Methods: cross sectional study among 300 adult female were selected among 8 villages of two district of Manipur. Self- structure interview questionnaire pre-tested was adopted questionnaire consist of socio-demographic profile, anthropometry status and risk factors of obesity. Data analysis was done using SPSS. Result: From the present study it is reported that majority 36.7% were in the age group 40-49 years, the mean height and weight of the female respondents were 150 cm and 59 kgs. The mean score of waist circumference was 83.2 cm and Waist Hip Ratio was .86cm additionally, the prevalence of overweight and obesity was 34.6% and 37.3% in the age group of 40-49 years. Eventually, to find the risk factor of obesity, there is significant association between activity pattern and obesity as the significant and P value is